Medicines dispensing in big pharmacies in Chile: ethical analysis about pharmaceutical chemist profession - Marín Toro, Adriana (Acta Bioethica, 2017)
Based on qualitative research, is described the context of dispensing drugs in “big pharmacy chains” in Chile, starring pharmaceutical chemists who have the role of technical directors of these entities. It is considered that the consumption and the economy are embedded in all the mechanisms of life, including health. Drugs in this sense, are a clear example of an everyday consumer object used by the chilean population, an issue which calls for a surveillance political, social and ethical about it. The social dimensions of the technical knowledge of pharmaceutical chemists are analyzed, based on the interests of pharmacies in which they are employed, a professional success measured in individual terms and achieving financial goals on health, an issue that encourages a culture that promotes the consumption of drugs, rather than restricting it. These professionals are part of a particular socio-economic and socio-political project capable even to modify the cognitive foundations of a profession.